2016
DOI: 10.1097/dss.0000000000000883
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind, Placebo-Controlled Pilot Study on the Use of Platelet-Rich Plasma in Women With Female Androgenetic Alopecia

Abstract: Platelet-rich plasma failed to demonstrate any statistically significant improvement in HMI or hair count in women with congenital female pattern hair loss. The patient survey results suggest a therapeutic advantage of PRP as perceived by patients but not according to hair count or HMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 11 publications
1
88
0
1
Order By: Relevance
“…In this study, however, only one treatment was administered and, of great importance, the PRP used was not activated, thereby impeding its full therapeutic potential. Nevertheless, they did document subjective improvement (such as less hair loss and improved hair thickness) [30]. In the studies where no statistical analysis was reported [12,32,35,36], the authors remarked positively on hair growth, volume, coverage, and mean hair density.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, however, only one treatment was administered and, of great importance, the PRP used was not activated, thereby impeding its full therapeutic potential. Nevertheless, they did document subjective improvement (such as less hair loss and improved hair thickness) [30]. In the studies where no statistical analysis was reported [12,32,35,36], the authors remarked positively on hair growth, volume, coverage, and mean hair density.…”
Section: Discussionmentioning
confidence: 99%
“…Further, neither a physician nor a subject self-assessment was performed. Another study, by Puig et al [30], did not detect significant improvement using objective measures (hair count or hair mass index) after PRP treatment. In this study, however, only one treatment was administered and, of great importance, the PRP used was not activated, thereby impeding its full therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations